Didaktik Metodik Masih Perlukah Sekarang? Sebuah Kajian terhadap Perkembargan Metodologi Pembelajaran di Sekolah - Yayat Suharyat (Turats, 2004)
Didactic method is a learning discipline oriented to give student teachers competence of teaching methodology. But connected w.th contemporary education issue, the existence of didactic method seems to be asked, whether It is still needed or not This papt:r has presented that didactic method is out of date, and then it should be changed by other up-to-date methods.